2019
DOI: 10.1086/704248
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Demethylating Effects of 5-aza-2′-deoxycytidine in Insects Requires a Whole-Genome Approach

Abstract: We previously demonstrated that treatment with the demethylating agent 5-aza-2′-deoxycytidine (5-aza-dC) alters the offspring sex ratios produced by females of the parasitoid wasp Nasonia vitripennis . Females allocate offspring sex ratio in line with Local Mate Competition theory, producing more or less female-biased sex ratios as the number of other females laying eggs on a patch varies, thereby reducing competition amongst their sons for mates. Interestingly, treatment with 5-aza-dC did not ablate the facul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
(68 reference statements)
0
6
0
3
Order By: Relevance
“…They all need to be present in cells at the S phase of the cell cycle to have an effect, which means that tissues undergoing rapid cell division may show preferential effects of these inhibitors. Treatment with these inhibitors has also been reported to cause hypermethylation of some loci [113], making interpretation of phenotypes and effects on gene expression difficult.…”
Section: How?mentioning
confidence: 99%
“…They all need to be present in cells at the S phase of the cell cycle to have an effect, which means that tissues undergoing rapid cell division may show preferential effects of these inhibitors. Treatment with these inhibitors has also been reported to cause hypermethylation of some loci [113], making interpretation of phenotypes and effects on gene expression difficult.…”
Section: How?mentioning
confidence: 99%
“…In terms of our own work on sex allocation, we have shown for example that facultative sex allocation under local mate competition is not associated with changes in gene expression [ 17 , 18 ], even though female oviposition of eggs is associated with major changes to the transcriptome (in particular, a down-regulation of metabolic processes: [ 17 , 54 ]). We have also shown though that disrupting patterns of DNA methylation changes the pattern of facultative sex allocation [ 85 , 86 ], suggesting that the regulation of gene expression via DNA methylation is important for facultative sex allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the systemic cytotoxic effects of these treatments are known from studies in other organisms, including Drosophila (Katz, 1985;Cunha et al, 2002). In these studies, the effects and toxicity of the drugs have been shown to be variable across developmental stages, tissues, and cell types (Laurent et al, 2010;Foret et al, 2012;Rasmussen et al, 2016;Cook et al, 2019) and also depend on the drug dosage (Yang et al, 2006;Cook et al, 2019). The study by Claudio-Piedras et al (2019) did not report toxicity in the mosquito An.…”
Section: Additional Layers Of Epigenetic Regulationmentioning
confidence: 99%
“…The mutagenic effects of this drug on DNA, which is the result of the formation of the Dnmt2nucleoside adduct and the subsequent repair, is expected to be proportional to the number of cytosines in the DNA that are targeted by Dnmt2. Therefore, such a global toxicity does not seem to agree with the Diptera's low Dnmt2 activity, and instead a marginal effect would be expected (Stresemann and Lyko, 2008;Cook et al, 2019). Beyond these initial observations, to validate the function of DNA methylation in mosquitoes, it will be necessary to silence the Dnmt2 enzyme, with iRNA or CRISPR/cas9, and to study the genome-wide effects at the level of DNA methylation, using bisulfite sequencing, and at the level of gene expression by RNA-seq.…”
Section: Additional Layers Of Epigenetic Regulationmentioning
confidence: 99%